The Design and Implementation of an Online Formative Assessment to Foster Interactive English Learning Among Senior High School Students in Indonesia - Sriyeni, Yeni; Sudimantara, Lala Bumela; Arrasyid, Farouk Imam (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
In response to pandemic-related learning loss, the Indonesian government has implemented a new English language curriculum with a focus on holistic assessment. However, the effectiveness of this curriculum relies on innovative teaching practices. This study positions the author as a curriculum engineer who has developed an online formative assessment concept. The aim of this research is to create a formative assessment tool that records student learning processes, promotes interactive English learning, and overcomes traditional pedagogical practices. By recording student learning processes and integrating technology, such as mind mapping and word clouds, students are able to explore, investigate, and generate new knowledge. The study follows a Research and Development (RD) approach and the developed website highlights the two online formative assessment methods. The findings demonstrate that using the online formative assessment tool can enhance students' critical thinking and communication skills while improving their English proficiency. Based on these results, this study recommends that schools integrate formative assessment tools into their English language curriculum to promote interactive learning and overcome traditional teaching practices. The findings of this study are relevant to educators, policymakers, and curriculum developers interested in promoting interactive English learning in a technology-enhanced learning environment. This study expected to be an assessment innovation in the interactive English.